Fenologia e predação em pré dispersão em Hancornia speciosa Gomes (APOCYNACEAE) - Pereira, Vitor Alberto de Matos (2022)
Hancornia speciosa, distributed in Bahia on sandy and poor soils of the Cerrado, Chapada Diamantina and coastal Restingas, represents an important food resource for fauna and humans, moving small local extractive chains. This study aimed to identify the phenological patterns of Hancornia speciosa Gomes populations located in Chapada Diamantina and Zona Costeira da Bahia and the environmental driving factors, seeking to confirm whether there is a similarity or not in fruiting between the two environments, in addition to describing the pre-dispersal predation process. A total of 108 individuals distributed equally across three subpopulations in Chapada Diamantina and three subpopulations in the Coastal Zone of the state of Bahia were monitored for 24 months. The frequency and intensity of the phenophases of budding, mature leaves, leaf fall, flower buds, flowering, immature and ripe fruits, in addition to the occurrence of predated fruits, were monitored. There was an advance in the average dates of all phenophases in Chapada Diamantina in relation to the Coastal Zone. There were no significant differences between the intensities of the phenophases of leaf fall, flowering, immature fruits and ripe fruits. It was not possible to identify distinct fruiting patterns between the two monitored regions with photoperiod and temperature being the main phenological drivers. For the first time, predation of immature fruits of H. speciosa by Asphondylia sp. (Cecidomyiidae) and Hypothenemus obscurus (Curculionidae), correlated with temperature and photoperiod, exerting population control pressure by reducing the availability of propagules and contributing to the maintenance of species diversity in the formations of H. speciosa. The study confirmed similar reproduction rates between populations of H. speciosa in different environments, suggesting that there are conservation mechanisms that overcome the edaphoclimatic disadvantages of the two regions.